2015
DOI: 10.1055/s-0035-1569145
|View full text |Cite
|
Sign up to set email alerts
|

Complications in CO2 Laser Transoral Microsurgery for Larynx Carcinomas

Abstract: Introduction Transoral laser microsurgery (TLM) has established itself as an effective option in the management of malignant tumors of the glottis, supraglottis, and hypopharynx. Nonetheless, TLM is not a harmless technique. Complications such as bleeding, dyspnea, or ignition of the air may appear in this type of surgery. Objective The aim of this study is to describe the complications that occurred in a group of patients treated for glottic and supraglottic carcinomas in all stages by TLM. Methods This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Aspiration was deemed a primary functional outcome measure of assessment. It was reported in 5 studies [11, 14, 1921]. In one paper, this was evaluated under direct visualization with a functional endoscopic examination of swallowing, where the authors documented liquid penetration.…”
Section: Resultsmentioning
confidence: 99%
“…Aspiration was deemed a primary functional outcome measure of assessment. It was reported in 5 studies [11, 14, 1921]. In one paper, this was evaluated under direct visualization with a functional endoscopic examination of swallowing, where the authors documented liquid penetration.…”
Section: Resultsmentioning
confidence: 99%
“…Nerurkar and Shah reported that the incidence of TG in patients who have undergone type IV TLM was 100%, and the study by Wang et al showed that the incidences of TG in patients who have undergone type IV and type V TLM were 78.6% and 80.0%, respectively [ 12 , 15 ]. Meanwhile, the incidence of chondronecrosis was not rare (1.02%), especially on whom the surgeon had to expose the thyroid cartilage during tumor resection in TLM [ 20 ]. These studies suggest that type IV or higher surgeries lead to a high likelihood of TG occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cervical complications after CO 2 TOLMS, Chiesa-Estomba et al reported infectious cervical complications in 2 (2%) patients—one had cervical abscess formation and another one was complicated by mediastinitis [80]. Peretti et al describe two cases of persistent cervical fistula after performing temporary tracheotomy in their patients [75].…”
Section: Complicationsmentioning
confidence: 99%
“…Peretti et al describe two cases of persistent cervical fistula after performing temporary tracheotomy in their patients [75]. Also, laryngeal vestibule stenosis after extensive laser resection of supraglottic tumor was described [77,80].…”
Section: Complicationsmentioning
confidence: 99%